Understanding the Potential of 2D Ga2O3 in Flexible Optoelectronic Devices: Impact of Uniaxial Strain and Electric Field. Issue 9 (19th July 2019) - Guo, Rui; Su, Jie; Lin, Zhenhua; Zhang, Junjing; Qin, Yu; Zhang, Jincheng; Chang, Jingjing; Hao, Yue
Abstract: The discovery of two‐dimensional (2D) Ga2 O3 has provided an effective way to further tune the performance of β‐Ga2 O3 . Understanding the effects of strain and electric field (E‐field) on 2D Ga2 O3 is helpful to explore the mechanism and potential application in the flexible device. Here, transport and optical properties of monolayer Ga2 O3 under uniaxial strain and E‐field are investigated. An indirect‐to‐direct band‐gap‐transition occurs under uniaxial tension due to the different variation of π bonding at the valence bands. The band‐gap exhibits a parabolic variation character from compression to tension, and relates to the direction of uniaxial strain. Interestingly, the transport characters are sensitive to the direction of uniaxial strain, and both compression and tension along b direction enhance the mobility of monolayer Ga2 O3, which is inconsistent with that of electron effective mass. The mobility of tensile monolayer Ga2 O3 can be enlarged to 48368.14 cm 2 V −1 s −1, different to that of 2D layered materials. Interestingly, the ultra‐visible absorption coefficients are just enhanced significantly by compression along c direction. Upon monolayer Ga2 O3 undergoes large E‐field (>0.5 eV Å −1 ), the band‐gap and anisotropic transport property decreases and even vanishes. The results are useful to reveal the mechanisms and potential of 2D Ga2 O3 in the flexible devices. Abstract : Uniaxial tensile can change the indirect character of monolayer Ga2 O3 into direct character. Both uniaxial compression and tension along b direction can enhance the mobility of monolayer Ga2 O3, and the mobility can be enlarged to 48 368.14 cm 2 V −1 s −1 . The anisotropic transport property and band gap can be significantly decreased and even vanished by external electric‐filed.